Enantiomeric Discrimination of Isoxazoline Fused β‐amino Acid Derivatives using (18‐Crown‐6)‐2, 3, 11, 12‐tetracarboxylic Acid as a Chiral NMR Solvating Agent. Issue 1 (14th November 2012) - Howard, Jessica A.; Nonn, Melinda; Fulop, Ferenc; Wenzel, Thomas J.
ABSTRACT (18‐Crown‐6)‐2, 3, 11, 12‐tetracarboxylic acid is a useful chiral NMR solvating agent for isoxazoline‐fused β‐amino acid derivatives. Isoxazoline substrates are analyzed as their hydrochloride salts in methanol‐d4. The crown ether and substrate associate through the formation of three hydrogen bonds between the protonated amine and crown ether oxygen atoms. Enantiomeric discrimination is observed for two or more resonances of every substrate. At least one of these resonances is free of overlap with other resonances in the spectrum and has large enough enantiomeric discrimination to enable the determination of enantiomeric purity. 2D COSY methods can be used to identify additional resonances that exhibit enantiomeric discrimination in the NMR spectrum. Chirality, 25:48‐53, 2013.© 2012 Wiley Periodicals, Inc.